Current State of Applications of Nanocellulose in Flexible Energy and Electronic Devices - Dias, Otavio Augusto Titton; Konar, Samir; Leão, Alcides Lopes [UNESP]; Yang, Weimin; Tjong, Jimi; Sain, Mohini (Frontiers, 2020)
Novel and unique applications of nanocellulose are largely driven by the functional attributes governed by its structural and physicochemical features including excellent mechanical properties and biocompatibility. In recent years, thousands of groundbreaking works have helped in the development of targeted functional nanocellulose for conductive, optical, luminescent materials, and other applications. The growing demand for sustainable and renewable materials has led to the rapid development of greener methods for the design and fabrication of high-performance green nanomaterials with multiple features, and consequently new challenges and opportunities. The present review article discusses historical developments, various fabrication and functionalization methods, the current stage, and the prospects of flexible energy and hybrid electronics based on nanocellulose.
Keywords: cellulose nanocrystals; cellulose nanofibrils; conductive materials; energy storage device; films; hybrid materials; luminescent materials; nanocomposites